17α-Ethinylestradiol in Lakes of Hanoi and its effect on seed germination. Issue 7 (14th September 2019) - Dang, Hieu M.; Nguyen, Ngan T. T.; Inagaki, Yoshihiko; Akkanen, Jarkko; Sakakibara, Yutaka
Abstract: The lakes of Hanoi are important water resources for urban agriculture. The concentrations of 17α-ethinylestradiol in the water of three major lakes were found to range from 0.1 to 9.1 ng/L, peaking during the rainy season. Effects at levels from 1 ng/L to 1 µg/L on the germination of mung bean ( Vigna radiata ) and bok choy ( Brassica rapa ) were studied. Soaking the seeds in solutions containing 17α-ethinylestradiol at 10 ng/L and higher increased the germination rate of mung bean but not of bok choy. For the latter, irrigation after sowing with solutions containing 17α-ethinylestradiol at 10 ng/L and higher accelerated germination. Abbreviations: MNRE: Ministry of Natural Resources and Environment; PE60 : Population equivalent; USGS: U.S. Geological Survey; SPE: Solid phase extraction; EDTA: Disodium ethylenediaminetetraacetate; HPLC: High performance liquid chromatography; ELISA: Enzyme-linked immunosorbent assay; DOM: Dissolved organic matter; EEQ: Estradiol equivalent